1984
DOI: 10.1104/pp.76.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen, Oxygen, and Carbon Isotope Ratios of Cellulose from Submerged Aquatic Crassulacean Acid Metabolism and Non-Crassulacean Acid Metabolism Plants

Abstract: ABSTRACIÌsotope ratios of cellulose and cellulose nitrate from aquatic Crassulacean acid metabolism (CAM) and DoD-CAM plants were determined. Cellulose oxygen istope ratios for all plants that grew together were virtuayl identical whereas large differences were observed for hydrogen Recently it has been shown that hydrogen isotope ratios of 'Abbreviations: PEP, P-enolpyruvate; SMOW, standard mean ocean water; PDB, Peedee belemnite. organic matter from terrestrial plants are also related to photosynthetic mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…Vallisneria spiralis Graeb. has not been specifically tested for CAM but Sternberg et al (1984) reported that the 14 C: 13 C ratio in tissues was lower than in the surrounding environment. Such preferential uptakes of ' 3 C are characteristic of CAM species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vallisneria spiralis Graeb. has not been specifically tested for CAM but Sternberg et al (1984) reported that the 14 C: 13 C ratio in tissues was lower than in the surrounding environment. Such preferential uptakes of ' 3 C are characteristic of CAM species.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few general surveys of CAM in native aquatic populations have been published (Keeley & Morton 1982;Sternberg et al 1984;Farmer & Spence 1985). This paper presents the first known survey of this kind in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well known separation of C3 plants from C4 and CAM plants based on stable carbon isotope ratios (17), oxygen and hydrogen isotope ratios ofcellulose and cellulose nitrate, respectively, also are influenced by photosynthetic mode (20,(22)(23)(24)(25). Analysis of C3, C4, and CAM plants growing in the vicinity of each other show that cellulose nitrate from CAM plants is enriched in deuterium relative to C3 and C4 plants (20, 22, 25).…”
mentioning
confidence: 99%
“…O processo de lignificação concentra C nos tecidos vegetais, de forma que quanto maior o teor de C, mais empobrecido torna-se o tecido em 13 C (Sternberg & Deniro, 1983;Sternberg et al, 1984). Verificou-se empobrecimento em 13 C na lignina nas espécies que compõem o CLU de 3,57 ‰ e nas que colonizam a FES de 2,30 ‰ (Quadro 5), em relação ao conjunto do tecido vegetal, e esse foi acima do preconizado por Eglin et al (2008), que foi de 1-2 ‰ de δ 13 C, com relação ao conjunto tecido vegetal.…”
Section: Composição Isotópica Da Lignina E Da Celulose Da Vegetaçãounclassified